LIGHT CURVE VARIATIONS OF THE MAGNETIC CATACLYSMIC BINARY MR SERPENTIS : PHOTOMETRIC PERIOD IS NOT AS SURE AS BELIEVED - Pavlenko, E. P.; Ketsaris, N. A.; Halevin, A. V.; Andronov, I. L. (Одеські астрономічні публікації, 2017)
The light curves show very large even for polars night-to-night variability of the amplitudes (from 0.4m to 1.6m) and shapes. The flares may be owed not only to the inhomogeneous accretion, but possibly some to the UV-Cet events. Large scatter of the phases does not allow to fit all observations even with one period, arguing for future monitoring.